Penerapan Evidence Based Nursing Practice (EBNP) Edukasi Video 5 Pilar terhadap Kadar Glukosa Darah Pasien Diabetes - Hentu, Ardin Saleh; Irawati, Diana; Anggareni, Dewi; Jumaiyah, Wati; Abriyanti, Rika Mustika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to identify the effectiveness of 5 pillars of education in controlling blood sugar levels. The method used in EBNP is a case study design. The application of EBNP begins with an article search by selecting articles that use the RCT method with the keyword